The Somatostatin Receptor-4 Agonist J-2156 Alleviates Mechanical Hypersensitivity in a Rat Model of Breast Cancer Induced Bone Pain - Shenoy, Priyank A.; Kuo, Andy; Khan, Nemat; Gorham, Louise; Nicholson, Janet R.; Corradini, Laura; Vetter, Irina; Smith, Maree T. (Frontiers in Pharmacology, 2018)
In the majority of patients with breast cancer in the advanced stages, skeletal metastases are common, which may cause excruciating pain. Currently available drug treatments for relief of breast cancer-induced bone pain (BCIBP) include non-steroidal anti-inflammatory drugs and strong opioid analgesics along with inhibitors of osteoclast activity such as bisphosphonates and monoclonal antibodies such as denosumab. However, these medications often lack efficacy and/or they may produce serious dose-limiting side effects. In the present study, we show that J-2156, a somatostatin receptor type 4 (SST4 receptor) selective agonist, reverses pain-like behaviours in a rat model of BCIBP induced by unilateral intra-tibial injection of Walker 256 breast cancer cells. Following intraperitoneal administration, the ED50 of J-2156 for the relief of mechanical allodynia and mechanical hyperalgesia in the ipsilateral hindpaws was 3.7 mg/kg and 8.0 mg/kg, respectively. Importantly, the vast majority of somatosensory neurons in the dorsal root ganglia including small diameter C-fibres and medium-large diameter fibres, that play a crucial role in cancer pain hypersensitivities, expressed the SST4 receptor. J-2156 mediated pain relief in BCIBP-rats was confirmed by observations of a reduction in the levels of phosphorylated extracellular signal-regulated kinase (pERK), a protein essential for central sensitisation and persistent pain, in the spinal dorsal horn. Our results demonstrate the potential of the SST4 receptor as a pharmacological target for relief of BCIBP and we anticipate the present work to be a starting point for further mechanism-based studies.